Preface - Jász, Judit (Acta Cybernetica, 2024)
The 13th Conference of PhD Students in Computer Science (CSCS) was organized by the Institute of Informatics of the University of Szeged (SZTE) and held in Szeged, Hungary, between June 29 - July 1, 2022.